Analyzing Digital Discourse New Insights and Future Directions - Bou-Franch, Patricia; Garcés-Conejos Blitvich, Pilar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'Taking a critical and situated perspective on social media platforms and communities, this cutting-edge volume lays down exciting new paths for future research on multimodality, the mediated co-construction of identity and sociability; and the discursive (re)construction of ideologies online. An absolute must-read for anyone interested in the development of the field of digital discourse studies.' -Caroline Tagg, the Open University, UK 'Analyzing Digital Discourse includes an exciting range of studies that go beyond the foci of many earlier studies: interrogating examples of digital discourse that range from parody Amazon reviews, profiles on LinkedIn to multi-semiotic data such as sexting messages, memes and emoji.' -Ruth Page, University of Birmingham, UK 'Examining issues at the forefront of current research, it offers new insights in global patterns and local details of digital discourse.' -Jannis Androutsopoulos, Universität Hamburg, Germany This innovative edited collection presents new insights into emerging debates around digital communication practices. It brings together research by leading international experts to examine methods and approaches, multimodality, face and identity, across five thematically organised sections. Its contributors revise current paradigms in view of past, present, and future research and analyse how users deploy the wealth of multimodal resources afforded by digital technologies to undertake tasks and to enact identity. In its concluding section it identifies the ideologies that underpin the construction of digital texts in the social world. This important contribution to digital discourse studies will have interdisciplinary appeal across the fields of linguistics, socio-linguistics, pragmatics, discourse analysis, gender studies, multimodality, media and communication studies. Patricia Bou-Franch is Professor of English at the University of Valencia, Spain. Pilar Garcés-Conejos Blitvich is Professor of English at the University of North Carolina at Charlotte, USA.
Part I. INTRODUCTION -- Chapter 1. Analyzing digital discourse: new insights and future directions; Patricia Bou-Franch and Pilar Garcés-Conejos Blitvich -- II. PAST, PRESENT AND FUTURE -- Chapter 2. The co-evolution of computer-mediated communication and computer-mediated discourse analysis; Susan C. Herring -- Part III. MULTIMODALITY -- Chapter 3. "Of course I'm married!" Communicative strategies and transcription-related issues in video-mediated interactions; Maria Grazia Sindoni -- Chapter 4. Multimodality in memes. A cyberpragmatic approach; Francisco Yus -- Chapter 5. Digital and written quotations in a news text: The Hybrid Genre of Political Opinion Review; Marjut Johansson -- Chapter 6. Emoticons in relational writing practices on WhatsApp: Some reflections on gender; Carmen Pérez-Sabater -- Part IV. FACE AND IDENTITY -- Chapter 7. From "My Manly Husband..." to "...Sitting Down to Take a Pee": The construction and deconstruction of gender in Amazon reviews; Camilla Vasquez and Addie Sayers China -- Chapter 8. Linguistic expert creation in online health practices; Marie-Thérèse Rudolf von Rohr, Franziska Thurnherr and Miriam A.Locher -- Chapter 9. How social media shape identities and discourses in professional digital settings: Self communication or self-branding?; Sandra Petroni -- Chapter 10. Losing Face on Facebook: Linguistic strategies to repair face in a Spanish common interest group; Carmen Maíz-Arévalo -- Part V. LANGUAGE AND MEDIA IDEOLOGIES -- Chapter 11. Sexting and hegemonic masculinity: Interrogating male sexual agency, empowerment and dominant gendered norms; Antonio García-Gómez -- Chapter 12. Twitter, politeness and self-presentation; Maria Sifianou and Spiridoula Bella -- Chapter 13. Pedagogy, Audience, and Attitudes: Influencing University Students' Metalinguistic Awareness about Texting Practices; Rebecca Roeder, Elizabeth Miller and Pilar Garcés-Conejos Blitvich.
Keywords: Linguistics -- Methodology; Pragmatics; Digital media; Communication; Computers and civilization; Sociolinguistics; Research Methods in Language and Linguistics; Pragmatics; Digital and New Media; Media and Communication; Computers and Society; Sociolinguistics